Development of a Learning Performance Assessment Framework for Phase A Students Aged 6–7 Years in Elementary Education - Nurjannah, Nurjannah; Syamsiatin, Eriva; Jarudin, Jarudin (Universitas Pattimura, 2025)
Assessing learning performance in Phase A students (6–7 years old) is crucial for promoting their cognitive, socio-emotional, and psychomotor development during this foundational stage of education. However, existing assessment frameworks often fail to address the holistic and developmental needs of this age group. This study aims to develop a comprehensive learning performance assessment framework tailored to Phase A students in elementary education. The framework was created through a systematic process involving a review of existing literature, expert judgment, and field testing in elementary schools. Its dimensions encompass cognitive skills, socio-emotional competencies, psychomotor skills, and creativity. Validation procedures included statistical analysis and expert panel reviews to ensure the framework’s reliability and applicability in diverse educational settings. The results demonstrate that the proposed framework effectively addresses existing gaps in assessment practices, providing educators with a robust tool to support holistic student development. The findings emphasize the importance of integrating multiple developmental dimensions into learning assessments and offer practical recommendations for classroom implementation. This study contributes to advancing educational assessment practices by advocating for tools aligned with the developmental characteristics of young learners. Future research should focus on longitudinal applications of the framework and its adaptability across various cultural and educational contexts.